THE PROBLEM OF SELF-ESTEEM OF PRIMARY SCHOOL CHILDREN AND FEATURES ITS FORMATION UNDER THE INFLUENCE OF TEACHER EVALUATION (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
Given article theoretically and empirically explores the problem of self-esteem. The author determines its main types, functions, analyzes in detail the views of domestic and foreign psychologists who have most fully developed its theoretical and practical aspects (V. James, A. Adler, C. Culi, D. Mid, K. Rogers, L. Vygotsky, S. L. Rubinstein and others). The author considers the features of the formation of self-esteem in the younger school age and its dependence on pedagogical evaluation. Also he emphasizes the exceptional importance of properly organized conditions for education and upbringing, within which a child can manifest himself as a full-fledged, socially active person who has an adequate self-esteem and is aware of his own worth and value to society.
Keywords: self-esteem, primary school age, pedagogical evaluation, psychological development.